Photocatalytic Nanoheterostructures and Chemically Bonded Junctions Made by Solution-Based Approaches. Issue 3 (4th May 2019) - Šutka, Andris; Järvekülg, Martin; Gross, Kārlis A.
Abstract: While single compound semiconductors were initially used for photocatalysis, combining two compounds to form a heterojunction significantly increases the photocatalysis performance. This review will outline how heterojunctions are superior, explain the different heterostructure architectures assembled from nanoparticles, and discuss the importance of achieving a large and quality contact in the junction, the heterojunction. Reference is made to methods for increasing the charge carrier performance and reducing recombination. Solution-based synthesis approaches, have been selected as the preferred route of manufacture, for the low cost scalability, and ability to combine a larger number of compounds. The main objective of this review article is to provide insight to the range of chemical solution-based methods for forming chemically bonded junction in nanoheterostructures for photocatalysis. Methods include chemical precipitation, impregnation, chemical bath deposition, hot injection, solvothermal, photo-deposition, electrochemical deposition, cation exchange and linker assisted assembly. The synthesis of different photocatalysts is addressed for each synthesis method. Solution synthesis is offered for coupling oxide semiconductors (i.e. TiO2, ZnO, WO3, Fe2 O3, BiVO4 ) with other oxides or metal chalcogenide quantum dots or metallic plasmonic nanoparticles.